Diverse vaginal microbiota in healthy Japanese women: a combined relative and quantitative analyses - Ito, Masahiro; Kataoka, Misaki; Sato, Yoichi; Nachi, Hideki; Nomoto, Koji; Okada, Nobuhiko (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThis cross-sectional study aimed to characterize the viable vaginal microbiota and identify host factors influencing this microbiota by employing a combination of relative and quantitative analyses.MethodsTwenty-four vaginal fluid samples were collected from healthy adult Japanese women for analysis. Vaginal fluid pH was measured using a portable pH meter. DNA was extracted from the vaginal fluid, and the 16S ribosomal RNA gene sequences in the V3-V4 regions were analyzed to identify bacterial species. Additionally, the vaginal fluid was cultured on four types of selective agar plates. The predominant species in the growing colonies were identified using colony polymerase chain reaction, and the colonies were counted.ResultsThe vaginal microbiota was classified into four categories based on the characterization of the dominant bacterial population: Lactobacillus crispatus, Lactobacillus iners, Lactobacillus gasseri, and a diversity group. The predominant bacterial species were consistent across methods; however, the levels of the viable population varied significantly. Body mass index had a significant influence on the total number of viable bacteria and vaginal pH, while age only affected vaginal pH.ConclusionsOur findings indicate that the vaginal microbiome of healthy Japanese women is not only highly diverse but also affected by host factors such as BMI and age.